TANGGUNG JAWAB HUKUM NEGARA ATAS TINDAKAN MELAWAN HUKUM YANG DILAKUKAN OLEH ANGGOTA KEPOLISIAN - Muhammad Syahril Ananda; Ardison Asri (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2025)
The Indonesian National Police (Polri) plays a central role in maintaining security, order, and law enforcement. However, unlawful acts by police officers can have broad legal consequences related to state responsibility. This study aims to identify the forms of unlawful acts committed by police officers that may incur state responsibility, and to analyze the state's legal accountability for these unlawful acts in Indonesia. This study uses a normative legal research method with a literature study approach. The data used are secondary data, collected through library research techniques. Data analysis was conducted qualitatively. Forms of unlawful acts by police officers that may incur state responsibility include: abuse of authority, excessive force and torture, arbitrary arrest and detention, and other general crimes committed in their capacity as officers. These forms of accountability include: (1) Individual Criminal Liability; (2) Administrative/Disciplinary Liability based on Police Regulation No. 7 of 2022 concerning the Indonesian National Police Professional Code of Ethics; and (3) Civil Liability.